Oracle against Israel"s social injustices: A rhetorical analysis of Amos 2:6−8 - Mamahit, Ferry Y. (HTS teologiese studies, 2010)
This article applied rhetorical analysis to an analysis of Amos’ prophetic oracle against Israel’s social injustices in Amos 2:6–8. The prophet uses a major rhetorical genre, namely judicial rhetoric, and several smaller rhetorical devices including the oracle against the nations, geographical chiasmus, numerical formula (the N+1 formula), the sevenfold structure, rhetorical entrapment, repetition, the war oracle, parallel structure and chiasms. These devices are utilised by Amos to make a persuasive appeal to his audience to respond to divine indictment.